Duodenal infusion of soy protein hydrolysate activates cAMP signaling and hypothalamic neurotransmitter synthesis in pigs. Issue 23 (8th November 2022) - Li, Zhongxin; Ding, Liren; Mu, Chunlong; Zhu, Weiyun; Hang, Suqin
Abstract : An increased soy protein hydrolysate (SPH) level promoted hypothalamic acetylcholine, dopamine, and brain-derived neurotrophic factor (BDNF) synthesis. Abstract : Neurotransmitters in the brain are important for cognition and memory. As bioactive substrates, whether increased soy protein levels in pigs can promote hypothalamic neurotransmitter synthesis remains unclear. The effect of increased soy protein hydrolysate (SPH) levels in the small intestine of pigs on neurotransmitter precursor supply, hypothalamic neurotransmitter synthesis and underlying molecular processes was investigated by using sixteen pigs (35.2 ± 0.3 kg) infused either with SPH (70 g day −1 ) or sterile saline (control) twice daily for 15 days via a duodenal fistula. It demonstrated that SPH infusion increased the expression of the neutral amino acid transporter B0AT1 in the jejunal mucosa, the serum tyrosine/large neutral amino acid ratio, the concentrations of serum tyrosine, hypothalamic tyrosine, dopamine and brain-derived neurotrophic factor (BDNF) ( P < 0.05). It also increased the jejunal and serum choline, hypothalamic choline and acetylcholine levels ( P < 0.05). Hypothalamic transcriptome revealed that differential genes were significantly enriched in the cholinergic synapse, dopaminergic synapse and cyclic adenosine monophosphate (cAMP) signalling pathways, and that the expression of key enzyme genes in the synthesis of acetylcholine and dopamine and dopamine receptors 1 (DRD1) was upregulated by SPH ( P < 0.05). Western blotting showed that SPH infusion activated the hypothalamic cAMP signalling pathways. Overall, SPH infusion promoted the synthesis of hypothalamic dopamine and acetylcholine, and the synthesised dopamine promoted BDNF production most likely through the activation of the cAMP signalling pathways by the DRD1.